Effects of a New Monetary Policy Loss Function in NEMO - Kathrine Lund; Ørjan Robstad (Norges Bank, 2012)
In this memo we provide technical documentation of the impulse responses to some representative shocks in NEMO. The impulse responses are shown both with the new specification of the monetary policy loss function presented in MPR 1/12 and with the specification used in the recent MPRs. The new monetary policy loss function entails a somewhat higher weight on output than the old. In addition, weight on deviations of the key policy rate from a simple rule in the old loss function is replaced by weight on deviations of the key policy rate from a normal level. In general, with the new loss function, the interest rate response to supply shocks will be smaller than with the old loss function. The interest rate responses to demand shocks have not changed much, while the response from an exchange rate shock is marginally smaller with the new loss function than with the old
hdl:11250/2507192
Keywords: 330